Electronic medical record data sharing scheme based on searchable encryption via consortium blockchain - Shufen NIU; Wenke LIU; Lixia CHEN; Caifen WANG; Xiaoni DU (Tongxin xuebao)
Considering that it was difficult to share medical record data among different medical institutions in cloud storage,an electronic medical record data sharing scheme based on searchable encryption on blockchain was proposed.In order to realize the secure storage and sharing of electronic medical records in the scheme,the patient’s electronic medical record ciphertext was stored in the hospital server,the ciphertext hash value was stored in the private blockchain,and the keyword index was stored in the consortium blockchain.Searchable encryption was used to implement secure search of keywords in the consortium blockchain,and proxy re-encryption technology was used to realize the sharing of electronic medical records of patients by other data users.Security analysis shows that the proposed scheme can achieve ciphertext security and keyword security.Moreover,the performance of the scheme was analyzed by function analysis,computational efficiency analysis and numerical simulation.The performance analysis shows that the scheme can achieve high computational efficiency.